Paget's disease of bone: A rare case in a patient under 40 years of age - Erina Melva McKinney; Anders R. Meyer; Elizabeth J. Friedman; Brian MacNeille Everist; Candice E. Rose (Elsevier, 2021)
Paget's disease of bone is a rare diagnosis in patients under 40 years of age. We report a case diagnosed in a 35-year-old patient with suspected symptomatic presentation at the age of 30 years during pregnancy. This report details the course of the patient's evaluation toward diagnosis and includes previously suspected etiologies, significant radiologic features and conclusive histologic findings. This case is relevant to the existing literature because it demonstrates that Paget's disease of bone should be included in the differential diagnosis of younger patients outside the traditional disease demographic who present with diagnostic radiologic findings and elevated serum alkaline phosphatase.